A Cross-Sectional Study of Associations Between Nonsynonymous Mutations of the BARD1 Gene and Breast Cancer in Han Chinese Women. Issue 4 (July 2013) - Liu, Hui; Zhang, Hengwei; Sun, Xianfu; He, Yaning; Li, Juntao; Guo, Xuhui
The PCR-PIRA and PCR-RFLP techniques were used for BARD1 genotyping. Correlations between gene polymorphisms and the susceptibility to breast cancer were analyzed by logistic regression analysis. Results showed that compared with the wild type of 378 Arg/Arg of BRAD1, the homozygotic type of 378 Ser/Ser with Arg378Ser site mutation had a protective effect (adjusted odds ratio: 0.628, 95% confidence interval: 0.306-1.145). Compared with individuals carrying the wild type of 24Pro/Pro, the disease risk of individuals with the heterozygous type of 24 Pro/Ser decreased by 30.6% and that with the mutational homozygotic type of 24 Ser/Ser decreased by 43.8%. SNP sites rs2229571 and rs1048108 of BARD1 are associated with a lower risk of breast cancer but not rs2070094.